2015
DOI: 10.1097/grf.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Breastmilk Expression and Breast Pump Technology

Abstract: More than 80% of mothers express milk at some point during the first 4 months postpartum. Many women rely on breast pumps to establish and maintain lactation particularly when the infant is not able to breastfeed. Proper breast pump fit and use are important to optimize breastmilk supply and prevent injury. As breast pumps continues to evolve and the number of women using them remains a substantial majority, health care professionals need to maintain a thorough understanding of this tool and relevant technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
15

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 39 publications
0
28
0
15
Order By: Relevance
“…Scenarios that complicate direct breastfeeding include infants with medical conditions that involve prolonged neonatal ICU admissions, inability for oral intake, difficulty latching or transferring milk, maternal comorbidities or postpartum complications, and physical separation of the lactating individual and infant, such as for work or travel. 48 In these scenarios, lactating individuals or other caretakers can feed an infant pumped breast milk through a bottle in place of direct breastfeeding. 48 Lactating mothers may thus express milk through direct breastfeeding, pumping, or some combination of the two.…”
Section: Lactation Physiologymentioning
confidence: 99%
See 3 more Smart Citations
“…Scenarios that complicate direct breastfeeding include infants with medical conditions that involve prolonged neonatal ICU admissions, inability for oral intake, difficulty latching or transferring milk, maternal comorbidities or postpartum complications, and physical separation of the lactating individual and infant, such as for work or travel. 48 In these scenarios, lactating individuals or other caretakers can feed an infant pumped breast milk through a bottle in place of direct breastfeeding. 48 Lactating mothers may thus express milk through direct breastfeeding, pumping, or some combination of the two.…”
Section: Lactation Physiologymentioning
confidence: 99%
“…48 In these scenarios, lactating individuals or other caretakers can feed an infant pumped breast milk through a bottle in place of direct breastfeeding. 48 Lactating mothers may thus express milk through direct breastfeeding, pumping, or some combination of the two. 49 The process of expressing all milk through pumping rather than direct breastfeeding is known as exclusive pumping.…”
Section: Lactation Physiologymentioning
confidence: 99%
See 2 more Smart Citations
“…11 Recent surveys confirm that lactation barriers remain across specialties. 6,[12][13][14] Studies have reported methods to improve lactation efficiency in mothers of neonatal intensive care unit (ICU) infants, [15][16][17] but none have examined lactation in resident physicians after return from maternity leave.…”
Section: Introductionmentioning
confidence: 99%